2016
DOI: 10.1002/ppap.201600062
|View full text |Cite
|
Sign up to set email alerts
|

How to produce an NOx- instead of Ox-based chemistry with a cold atmospheric plasma jet

Abstract: A novel method is presented, which allows to generate a nitrogen oxides (NOx)‐dominated chemistry with a cold atmospheric plasma (CAP) jet which typically produces an oxygen‐based reactive species (Ox) cocktail. The reactive oxygen and nitrogen (RONS) production of the CAP jet kinpen is monitored using Fourier transform infrared (FTIR) absorption spectroscopy. While in previous approaches, the plasma chemistry of CAP jets operated with noble gases has been influenced with molecular feed gas admixtures of O2 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
72
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 75 publications
(74 citation statements)
references
References 55 publications
(101 reference statements)
0
72
1
1
Order By: Relevance
“…In the following, possible reaction mechanisms that can lead to the generation of NO in systems are discussed. In the first paragraph below, the solvation of gaseous NO in the liquid is analysed since it is known from the literature 5,44 that the investigated plasma source produced NO in the gas phase. This process could be excluded as the predominant process for the origin of the liquid phase NO.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the following, possible reaction mechanisms that can lead to the generation of NO in systems are discussed. In the first paragraph below, the solvation of gaseous NO in the liquid is analysed since it is known from the literature 5,44 that the investigated plasma source produced NO in the gas phase. This process could be excluded as the predominant process for the origin of the liquid phase NO.…”
Section: Resultsmentioning
confidence: 99%
“…A previous study by Schmidt-Bleker et al has shown that the generation of NO x in the gas phase by the kINPen operated with an O 2 /N 2 feed gas admixture can be enhanced by humidifying the feed gas. 5 That study has also shown that NO can also be detected in the far field (12 mm or more in front of the nozzle 5 ) of the jet, if the feed gas is humidified and a N 2 gas curtain is applied. However, it is noted that in the near field (from the nozzle until 12 mm 1 ) (6) and 7), the detected downstream nitrogen oxides (H x NO y ) are an indicator of the presence of NO in the effluent.…”
Section: Solvation Of Gaseous Nomentioning
confidence: 91%
See 1 more Smart Citation
“…Over the throttle valve, the gas produced by the plasma source in its controlled atmosphere was aspirated into the multi-pass cell. Figure 2 depicts the overall setup that has previously been used e.g., in [26]. The measurement captured a wavenumber range of 700 to 4000 cm −1 , which allowed the detection of several nitrogen compounds such as nitric oxide (NO) and nitrous oxide (N 2 O) in addition to the expected most abundant species O 3 and NO 2 in the far-field.…”
Section: Determination Of Produced Species Densitiesmentioning
confidence: 99%
“…Third, clinical plasma medicine without support, monitoring, and supervision by scientific plasma research jeopardizes the benefit of patients and deceives their trust in medical professionalism. The role of clinicians on the way to EBM in plasma medicine is to ask the right questions to stimulate basic research …”
Section: Introductionmentioning
confidence: 99%